Home and leisure activities and childhood knee injuries. - Moustaki, M.; Pitsos, N; Dalamaga, M; Dessypris, N; Petridou, E (Injury, 2005)
AIM: To assess the relative occurrence of non motor-vehicle knee injuries and identify important clusters that can be targeted for preventive interventions. METHODS: The study subjects covered 2167 children (0-14 years) who suffered non motor-vehicle knee injuries out of 66870 registered during a three-year period in an established Emergency Department Injury Surveillance System (EDISS). A more serious joint injury was identified in 263 (12%) children, whereas the remaining 1904 children had only soft tissue knee injuries. RESULTS: The incidence of non motor-vehicle knee injuries was estimated at 6.5 per 1000 children-years. Both the incidence of knee injuries and the male-to-female ratio increase with increasing age, reflecting the gender and age pattern of physical activity. Three clusters were identified: The first consisted of more serious knee injuries among older children, frequently resulting after a fall from stairs or a collision in school during winter months; the second cluster consisted of rather minor knee injuries occurring mostly among younger girls at home or in playgrounds, following a fall after stumbling or hit by an object while playing, especially during the summer; the third cluster comprised injuries among older boys, sustained mainly subsequent to overexertion in a sports area. CONCLUSION: Knee injuries tend to be more common among boys but more serious among girls. More and less serious knee injuries tend to fall into distinct clusters that could facilitate prioritization of preventive measures.
Keywords: Accidents; Accidents, Home; Adolescent; Age Distribution; Child; Child, Preschool; Cluster analysis; Female; Greece; Humans; Infant; Infant, Newborn; Knee Injuries; Leisure Activities; Male; Prevalence; Sex Distribution